การพัฒนาทักษะด้านความเชื่อและจินตนาการของนักแสดง: กรณีศึกษา แมรี่ แอนน์ ในบทละครเรื่อง ฤกษ์รัก ของ นิค เพย์น - ธัญวรัตน์ แสงสุวรรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2023)
The study hypothesized that the practice of the concepts of belief and imagination can improve an actor s performance by allowing them to tune in to the character of Marianne from Constellations on a profound level. The researcher analyzed and interpreted the role through various acting exercises, including Stanislavski’s Magic If technique, Chekhov s acing techniques, and improvisation. Also, observing and recording the outcomes of the exercises are among the sources of data gathered by the researchers. Besides, data were also gathered from a questionnaire, interviews with performance specialists, and the personal experiences of the researcher throughout all exercises. The results from 65 audiences responding to the questionnaire agreed that the researcher has the belief and imagination to access the role, which enhances the performance and makes the character s conflicts more interesting. The average mean score of agreement is 3.98 out of 5. This suggests the acting exercises are effective at enhancing the actor s belief and imagination, which enables the actor to better connect with the character. The results of the workshop indicate that the "Magic If" technique is the most effective strategy when incorporated with improvisation and Chekhov s techniques, as they help the actor tune into the character and generate the belief and imagination necessary to enhance the performance.